IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PEMBENTUKAN KARAKTER SISWA - Putri, melani mandasari; Okto Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education in Indonesia faces challenges in shaping students' characters amidst the phenomenon of permissive education and character crisis. This study aims to explore the implementation of the Pancasila Student Profile Strengthening Project and dance extracurricular activities in shaping students' characters at SD Negeri 1 Karangmangu. The method used is a qualitative approach with a case study, involving observation, interviews with the principal, 2 teachers, 1 trainer and 6 students. Primary data were collected from six students who were active in the Pancasila Student Profile Strengthening Project and dance extracurricular activities, while secondary data were obtained from related literature. The results of the study indicate that the implementation of the Pancasila Student Profile Strengthening Project integrated with dance extracurricular activities has succeeded in shaping students' characters, namely honest, disciplined, hard-working, creative, democratic, patriotic, communicative, socially caring, and responsible. Students showed an increase in positive attitudes and achievements, including success in dance competitions. This study emphasizes the importance of integrating Pancasila values ​​in the curriculum and extracurricular activities as an effective strategy in shaping students' characters. It is hoped that the results of this study can be a reference for other schools in implementing character education based on culture and local wisdom.